2009
DOI: 10.1093/ndt/gfp532
|View full text |Cite
|
Sign up to set email alerts
|

Functional polymorphisms in transforming growth factor-beta-1 (TGF -1) and vascular endothelial growth factor (VEGF) genes modify risk of renal parenchymal scarring following childhood urinary tract infection

Abstract: Activating variants in the TGFbeta-1 and VEGF gene promoters are associated with post-UTI renal scar formation in children. The TGFbeta-1 509T allele predicts renal scarring independent of VUR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 42 publications
2
36
1
Order By: Relevance
“…Although we have not analyzed genetic susceptibility as the risk factor for ASL and USF several reports demonstrated the role of genetic susceptibilities as clinical determinants explain only a portion of individual risk [25]. Meta-analysis by Zaffanello et al revealed association between renal scarring formation after UTI and angiotensin enzyme insertion/deletion polymorphism or transforming growth factor-beta 1 c.509 T>C polymorphism [3,9,25].…”
Section: Discussionmentioning
confidence: 89%
“…Although we have not analyzed genetic susceptibility as the risk factor for ASL and USF several reports demonstrated the role of genetic susceptibilities as clinical determinants explain only a portion of individual risk [25]. Meta-analysis by Zaffanello et al revealed association between renal scarring formation after UTI and angiotensin enzyme insertion/deletion polymorphism or transforming growth factor-beta 1 c.509 T>C polymorphism [3,9,25].…”
Section: Discussionmentioning
confidence: 89%
“…Genotype-phenotype analyses suggest that the C allele VEGF þ405G>C is associated with decreased promoter activity and decreased expression of VEGF, as the C allele reduces binding of the transcription factor, MZF1, which then subsequently reduces gene expression (72)(73)(74). Hence, the C allele VEGF þ405G>C may confer a survival advantage by reducing a tumor's ability to stimulate angiogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies questioned the significance of ACE gene polymorphism as an independent risk factor for the development and progression of RN (Dudley et al, 2002;Pardo et al, 2003). An association between TGF-1 gene polymorphism and the risk of renal scarring in patients with vesicoureteral reflux was also disclosed Kowalewska-Pietrzak et al (2008), whereas Hussein et al (2010) demonstrated an association between vascular endothelium growth factor (VEGF) gene polymorphism and the risk of the development of RN.…”
Section: Reflux Nephropathymentioning
confidence: 99%
“…An association between polymorphism of angiotensin-converting enzyme gene and renal scarring was demonstrated (Haszon et al, 2002;Hohenfellner et al, 1999;Ohtomo et al, 2001;Ozen et al, 1999;Pardo et al, 2003). Similarly, polymorphism of transforming growth factor gene (Kowalewska-Pietrzak et al, 2008;Hussein et al, 2010) and polymorphism of vascular endothelium growth factor gene (Hussein et al, 2010) had impact on severity of renal scarring. Post-inflammatory nephropathy may be classified into reflux nephropathy due to vesicoureteral reflux and obstructive nephropathy due to urinary tract obstruction (Marra et al, 2004;Orikasa et al, 1995;Smellie et al, 1981).…”
Section: Urinary Tract Infections 310mentioning
confidence: 99%